The P4 Study: Postpartum Maternal and Infant Faecal Microbiome 6 Months After Hypertensive Versus Normotensive Pregnancy - Susic, Daniella Frances; Wang, Leanne; Roberts, Lynne Margaret; Bai, Michelle; Gia, Andrew; McGovern, Emily; Jiang, Xiao-Tao; Davis, Gregory K.; El-Omar, Emad; Henry, Amanda (Frontiers in Cellular and Infection Microbiology, 2022)
Objective/Hypothesis To explore potential differences in faecal microbiome between women, and their infants, who had normotensive pregnancies (NP) and those who had a hypertensive pregnancy (HP), either gestational hypertension (GH) or preeclampsia (PE). Methods This is a sub study of P4 (Postpartum Physiology, Psychology, and Paediatrics Study) and includes 18 mother-infant pairs: 10 NP and 8 HP (HP as defined by blood pressure > 140/90mmHg; of which 6 had PE, and 2 GH), six months postpartum. The participating mothers collected stool samples from themselves and their infants. 16S rRNA V3-V4 amplicons were used to study the faecal microbiome. Results The sample of women and their infants were mostly primiparous (n =16) with vaginal birth (n = 14). At the time of faecal sampling 8 women were using hormonal contraception, and one HP woman remained on an antihypertensive. All women had blood pressure < 130/80mmHg, and 10 had high BMI (> 30). All infants had started solids, 8 were exclusively breastfed, 1 exclusively formula fed and 9 both. Three infants had been exposed to a course of antibiotics. Six months postpartum, there were no significant differences in alpha or beta diversity between the gut microbiota of HP and NP women (P > 0.05). However, a statistically significant difference was detected in alpha diversity between infants following HP and NP, with lower diversity levels in HP infants (P < 0.05). It was also found that at a genus and species level, the gut microbiota of HP women was enriched with Bifidobacterium and Bifidobacterium sp. and depleted in Barnesiella and Barnesiella intestinihominis when compared to NP women (P < 0.05). Similarly, the gut microbiota of infants born from HP was enriched in Streptococcus infantis and depleted in Sutterella, Sutterella sp., Bacteroides sp. and Clostridium aldenense compared to infants born from NP (P < 0.05). Discussion While our findings are at best preliminary, due to the very small sample size, they do suggest that the presence of hypertension in pregnancy may adversely affect the maternal microbiota postpartum, and that of their infants. Further analysis of postpartum microbiome data from future studies will be important to validate these early findings and provide further evidence about the changes in the microbiota in the offspring of women following hypertensive disorders of pregnancy (HDP), including possible links to the causes of long-term cardiovascular disease, the prevalence of which is increased in women who have experienced HDP.